Assessment of second-order Møller-Plesset perturbation theory for isomerization and dissociation energies of nitramide. (March 2020) - Yu, T; Liu, Y Zh; Lai, W P; Ma, Y D; Ge, Zh X
Abstract: Based on the optimized molecular geometries at the B3LYP/cc-pVDZ level, the electronic and nuclear repulsion energies of nitramide (NH2 NO2 ), O-nitrosohydroxylamine (NH2 ONO), 1-hydroxydiazene 1-oxide (NH=N(O)OH), the transition state between NH2 NO2 and NH2 ONO, the transition state between NH2 NO2 and NH=N(O)OH, NH2 radical, NO2 radical, H2 O, N2 O, H2, N2, O2, H, N and O were calculated by various second-order Møller–Plesset perturbation theory (MP2) methods. The domain based local pair natural orbital (DLPNO), explicitly correlated F12, density fitting (RI), spin-component scaled (SCS) and orbital optimized (OO) calculations were employed in MP2 calculations. The isomerization and dissociation energies of NH2 NO2 were estimated by CCSD(T)-F12-RI as benchmark method. The testing results indicate that the deviations can be reduced by SCS method efficiently.